Pluralismo e reciprocidade : um ensaio sobre as motivações para o liberalismo político - Fanton, Marcos (2014)
The current debate on the motivation for the endorsement and defense of a liberal political conception is divided basically into two positions: the first defends the need for a moral foundation, capable of giving reasons for individuals endorse this political conception, the second is stablished directly from the domain of the political, leaving the problem of motivation as a subsequent argument. Philosophers such as Charles Larmore and Ernst Tugendhat are bind to the first position, while John Rawls to the second. Based on this, we intend to show how the readings of the first two philosophers on the work of the latter are mistaken, given the non-observance of the points of view set forth in justice as fairness. After this clarification, we analyze the idealized point of view of the citizens of a well-ordered society established in Rawls' theory of justice. The interpretation of this topic shows how the problem of motivation, to this author, is based on conceptions and ideals, not on principles. Finally, it discusses one of the arguments for the stability of justice as fairness, the acquisition of a sense of justice, in order to verify if Rawls can avoid an explanation of the motivation to act accordingly with the political conception of justice which remains in the political domain. My thesis is that the answer should be negative, in consideration of the moral psychology of the reasonable, based on the psychological principle of reciprocity. There, Rawls conceives a comprehensive view of the human being which can be summarized in the figure of reciprocity rider.